P=25,000÷(1+0.0425)^(18)
P=11,818.73
So the answer is b
Answer:
4 and -4
Step-by-step explanation:
n^-2 = 1/16
Negative power rule:
(4)^-2 = 1/4²
= 1 /16
(-4)^-2= (-1)²/4²
= 1 /16
Answer:
-k-14
Step-by-step explanation:
Use distributive property and then just carry on and combine like terms.
Answer:
(f - g)(x) = 3x² - 2x - 6
General Formulas and Concepts:
<u>Pre-Alg</u>
- Order of Operations: BPEMDAS
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x² - 2
g(x) = 2x + 4
(f - g)(x) is f(x) - g(x)
<u>Step 2: Evaluate</u>
- Substitute: (f - g)(x) = 3x² - 2 - (2x + 4)
- Distribute -1: (f - g)(x) = 3x² - 2 - 2x - 4
- Combine like terms: (f - g)(x) = 3x² - 2x - 6